Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

y=x-3
y+3x=1 solve by substitution


Sagot :

mj3mar

Answer:

x = 1

Step-by-step explanation:

x - 3 + 3x = 1

4x - 3 = 1

4x = 4

x = 1

Answer:

x=1, y=-2

Step-by-step explanation:

According to the substitution property, if x = y, then x can be substituted for y in any equation, and y can be substituted for x in any equation.

We are already given the values:

y=x-3

y+3x=1

We can substitute y into the equation.

As so-

[tex]x-3+3x=1[/tex]

Combine common terms:

[tex]4x-3=1[/tex]

Now solve for x. To solve for a variable, we must isolate it:

Add 3 to both sides:

[tex]4x=4[/tex]

The last thing, 4 is being multiplied to x, so we must divide it to both sides to isolate the variable.

[tex]x=1[/tex]

Now we can just substitute the x value into the y equation:

[tex]y=x-3\\y=1-3\\y=-2[/tex]

It is always better to check our answers, we can substitute our x and y into the equation:

[tex]-2+3(1)=1\\-2+3=1\\1=1[/tex]

We are right! :)) Hope it helps!

x=1, y=-2

(1,-2)

We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.